2012
DOI: 10.1146/annurev-economics-080511-110909
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Economics and Psychology of Incentives

Abstract: Monetary incentives can backfire while nonstandard interventions, such as framing, can be effective in influencing behavior. I review the empirical evidence on these two sets of anomalies. Paying for inherently interesting tasks, paying for prosocial behavior, paying too much, paying too little, and providing too many options can all be counterproductive. At the same time, proper design of the decision-making environment can be a potent way to induce certain behaviors. After presenting the empirical evidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
0
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(173 citation statements)
references
References 125 publications
(106 reference statements)
5
159
0
9
Order By: Relevance
“…As we will show in this section, work effort can even bring positive utility of fulfi lling intrinsic motivation, m, to some workers (or under some circumstances). If we have i = {g} just like in the gift exchange case, we get c(e i |i) < 0 (Gneezy, Meier, & Rey-Biel, 2011;Kamenica, 2012). In this framework the workers' effort is not so much infl uenced by extrinsic motivation such as money or extensive oversight by the employers, it can even be destroyed by them.…”
Section: Extrinsic and Intrinsic Motivation Crowding Outmentioning
confidence: 89%
See 1 more Smart Citation
“…As we will show in this section, work effort can even bring positive utility of fulfi lling intrinsic motivation, m, to some workers (or under some circumstances). If we have i = {g} just like in the gift exchange case, we get c(e i |i) < 0 (Gneezy, Meier, & Rey-Biel, 2011;Kamenica, 2012). In this framework the workers' effort is not so much infl uenced by extrinsic motivation such as money or extensive oversight by the employers, it can even be destroyed by them.…”
Section: Extrinsic and Intrinsic Motivation Crowding Outmentioning
confidence: 89%
“…The standard economic model, which explains employee's effort only through the wage (determined by productivity), is therefore incomplete. In particular, it does not consider that incentives to work do not have to be monetary; in other words, that there are other things besides the disutility of labour ( (Kamenica, 2012) and section 1.3 here). This perspective article aims to make the simple labour economic model more realistic in order to account for the mounting empirical evidence, which might otherwise be dismissed as anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Work in decision sciences (incl., psychology, behavioral economics, economics, management) has often shown that the presentation of monetary incentives can actually have a detrimental rather than corrective or positive effect on decision-making performance (for review see Kamenica, 2012). The speculation is that financial incentives interfere with personal intrinsic motivations to perform a given task (Ariely, Gneezy, Loewenstein, & Mazar, 2009;Bahrick, 1954;Eisenberger & Cameron, 1996;Kamenica, 2012;Lepper, & Greene, 2015;McGraw, 1978;Deci & Ryan, 1985).…”
Section: The Role Of Rewards In Judgment and Decision-makingmentioning
confidence: 99%
“…It is a well-known empirical insight in behavioral economics that hard incentives of this type may have unintended consequences (Kamenica 2012). A popular example is the observation by Gneezy and Rustichini (2000) that a fine intended to discourage immoral behavior may be 46 See e.g.…”
Section: Incentives and Rewardsmentioning
confidence: 99%
“…Mill therefore goes a step further than Smith, in offering explanations in terms of incentives for the supposedly low quality of collective action, such as governments crowding out the informal institutions underlying voluntary cooperation. 6 See also Kamenica (2012). 7 On Smith in this context see also Buchanan (1976).…”
Section: Introductionmentioning
confidence: 99%